2003
DOI: 10.1111/1467-9922.00210
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Input and The Incorporation of Feedback: An Exploration of NS–NNS and NNS–NNS Adult and Child Dyads

Abstract: Given the documented benefits of participation in communicative interaction (e.g., Gass & varonis, 1994; Mackey, 1999), the present study investigated the effects of interlocutor type on the provision and incorporation of feedback in task–based interaction. The interactions of 48 dyads, evenly divided among adults and children, and native speaker–nonnative speaker and nonnative speaker–native speaker, were analyzed to assess the effect of interlocutor on (1) amount of feedback, (2) opportunities for modified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
140
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(150 citation statements)
references
References 55 publications
6
140
2
2
Order By: Relevance
“…She found that NNS-NNS combination provided more opportunities of CF and NoM in comparison to NS-NNS combination. Other studies, such as Mackey, Oliver, & Leeman (2003) and Varonis & Gass (1985) show positive outcome in adult peer interaction. However, unlike our study, all adult learners recruited were from the same L2 language proficiency levels.…”
Section: Previous Studiesmentioning
confidence: 84%
See 2 more Smart Citations
“…She found that NNS-NNS combination provided more opportunities of CF and NoM in comparison to NS-NNS combination. Other studies, such as Mackey, Oliver, & Leeman (2003) and Varonis & Gass (1985) show positive outcome in adult peer interaction. However, unlike our study, all adult learners recruited were from the same L2 language proficiency levels.…”
Section: Previous Studiesmentioning
confidence: 84%
“…Oliver (1998) explores the effects of peer learning in school aged-children involving NS-NNS and NNS-NNS combinations. She found that similar to adults, children used variety of negotiation strategies during their interaction which could facilitate L2 learning, while other studies (e.g., Lyster & Ranta, 1997;Mackey & Oliver, 2002;Mackey, Oliver, & Leeman, 2003;Oliver, 2002) examine the interaction between adult NS and child NNS. Many more studies explore the interaction in learner-learner combination.…”
Section: Previous Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Literature on monolingual interactions in pluricultural contexts is very wide and deals with native speakers -non-native speakers (NS-NNS) interaction (PICA, 1994;SHEHADEH, 1999;WIBERG, 2003;SEIDLHOFER, 2001;GONZALEZ-LLORET, 2005;ROGERSON-REVEL, 2006;SWEENEY;ZHU, 2010;DOBAO, 2012) and non-native speakers -non-native speakers (NNS-NNS) interaction (SCHWARTZ, 1980;VARONIS;GASS, 1985;YULE, 1990, PICA;LINCOLN-PORTER;PANINOS;LINNEL, 1996;GARCÍA MAYO;PICA, 2000;MEIERKORD, 1996MEIERKORD, , 1998MEIERKORD, , 2000MACKEY;OLIVER;LEEMAN, 2003, AL-GHATANI;ROEVER, 2012;COGO;DEWEY, 2012), indicating that not only the context of face-to-face interaction but also the setting, the scene and the relationship between interlocutors influence the structure of the negotiation. However, if one of the speakers is using a foreign language, the language deficit determinates what can be said and how it is said, and the unbalanced linguistic proficiency between them (either in NS-NNS interactions and NNs-NNs)…”
Section: From Monolingual To Plurilingual Interactionsmentioning
confidence: 99%
“…Researchers of interaction involving foreign language leaming have mostly used artificial settings, for instance, they form pairs of native and non-native speakers who have to discuss a particular task {Porter, 1986, andMackey, Oliver, &Leeman, 2003, are just two examples). Moreover, studies tend to concentrate on grammatical, conversational and vocabulary skills of a general nature, rather than analyse conversations in the context of teaming specific content and studying the influence of subject matter on the conversations (cf.…”
Section: Introductionmentioning
confidence: 99%